1994
DOI: 10.1021/bi00255a024
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Study of the Active Site of Coprinus cinereus Peroxidase

Abstract: Resonance Raman (RR) spectra for the resting state ferric and the reduced ferrous forms of recombinant Coprinus cinereus peroxidase (CIP), obtained with different excitation wavelengths and in polarized light, are reported. The spectra are compared with those obtained previously for cytochrome c peroxidase expressed in Escherichia coli [(CCP(MI)] and horseradish peroxidase (HRP-C). Although the enzymic properties of CIP and HRP-C are similar, the RR data show that, in terms of the heme cavity structures, CIP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
76
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 47 publications
15
76
1
Order By: Relevance
“…The m(C=C) vinyl stretching modes are enhanced via the A-term (Franck-Condon mechanism); however, these bands are also observed in Q band excitation. This is consistent with previous observations for various heme containing peroxidases-namely CcP [24], HRPC [25], and Coprinus cinereus peroxidase (CIP) [26]-despite the fact that vinyl stretching modes are not expected to be enhanced a priori with visible excitation. The complete assignment of the high-frequency region is reported in Table S1 of the ESM.…”
Section: Spectroscopy At Room Temperaturesupporting
confidence: 92%
“…The m(C=C) vinyl stretching modes are enhanced via the A-term (Franck-Condon mechanism); however, these bands are also observed in Q band excitation. This is consistent with previous observations for various heme containing peroxidases-namely CcP [24], HRPC [25], and Coprinus cinereus peroxidase (CIP) [26]-despite the fact that vinyl stretching modes are not expected to be enhanced a priori with visible excitation. The complete assignment of the high-frequency region is reported in Table S1 of the ESM.…”
Section: Spectroscopy At Room Temperaturesupporting
confidence: 92%
“…The structure at pH 4.5 presented here may represent the physiological form of the resting enzyme and is the first example of a peroxidase with a typical pentacoordinated heine iron demonstrated by crystallography. This is consistent with the resonance Raman and NMR studies done on C. einereus peroxidase which showed that at a neutral pH the ferric state is characteristic of a fivecoordinated high-spin heme [26,27]. In CcP, LiP, MnP, and ascorbate peroxidase, a water molecule occupies the 6th position of each heme [14][15][16][17].…”
Section: Coordination To the Heme Ironsupporting
confidence: 85%
“…6, together with those of native ferrous HRPC and its imidazole complex, for 441.6 nm excitation, where the HS form is selectively resonance-enhanced. The spectrum of the native protein recorded at 441.6 nm is essentially identical to that reported previously for excitation at 457.9 nm (36) and is characteristic of a 5-c HS heme. The same experiment was also carried out with 413.1 nm excitation, where the LS form is selectively resonance enhanced (data not shown).…”
Section: Carbon Monoxide and Bha Binding To Casupporting
confidence: 80%